2014
DOI: 10.1111/1469-0691.12259
|View full text |Cite
|
Sign up to set email alerts
|

Viral load and humoral immune response in association with disease severity in Puumala hantavirus-infected patients—implications for treatment

Abstract: Hantaviruses are the causative agents of haemorrhagic fever with renal syndrome (HFRS) in Eurasia and of hantavirus cardiopulmonary syndrome (HCPS) in the Americas. The case fatality rate varies between different hantaviruses and can be up to 40%. At present, there is no specific treatment available. The hantavirus pathogenesis is not well understood, but most likely, both virus-mediated and host-mediated mechanisms are involved. The aim of the present study was to investigate the association among Puumala han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 30 publications
4
54
1
1
Order By: Relevance
“…A correlation between high levels of viremia and severity of the disease has been described in previous studies for SNV Virus [Xiao et al, ] and DOBV virus [Saksida et al, ]. A recent report [Pettersson et al, ] asserts that there was a tendency for a higher PUUV RNA load in patients with non‐severe/severe illness during the first 0–3 days. There were no significative differences between non‐severe/ severe cases or between fatal/ non‐fatal cases analyzed in the present study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A correlation between high levels of viremia and severity of the disease has been described in previous studies for SNV Virus [Xiao et al, ] and DOBV virus [Saksida et al, ]. A recent report [Pettersson et al, ] asserts that there was a tendency for a higher PUUV RNA load in patients with non‐severe/severe illness during the first 0–3 days. There were no significative differences between non‐severe/ severe cases or between fatal/ non‐fatal cases analyzed in the present study.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies of viremia in HPS and hemorrhagic fever with renal syndrome (HFRS) suggested an association between initial high viral load of Dobrava (DOBV) [Saksida et al, ], Sin Nombre (SNV) [Terajima et al, ] and Puumala (PUUV) [Pettersson et al, ] viruses, and a severe clinical outcome. Sex‐related differences in susceptibility to virus infection and disease outcome have been proposed but not extensively studied [Martinez et al, ; Klein et al, ; Brundin et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…There are also a number of variables, such as low specific immunoglobulin G titer, that potentially predict severe disease [47] but are not included in this study. Further, the findings show only associations between the different variables in patients with acute PUUV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although hantaviral disease shows high variability in the intensity and manifestation of symptoms, endothelial dysfunction seems to be the common underlying mechanism of hantavirus infection. Viral replication and im-mune-mediated effects both contribute to tissue damage in hantavirus infection, and the mechanisms of regenerative repair are not known (35)(36)(37)(38)(39)(40)(41)(42). Therefore, we analyzed the role of EPCs in the clinical course of hantavirus infection.…”
mentioning
confidence: 99%